The interventional effects of loving-kindness meditation on positive emotions and interpersonal interactions - He X (Dove Medical Press, 2015)
Xiaoli He,1 Wendian Shi,2 Xiangxiang Han,1 Nana Wang,1 Ni Zhang,1 Xiaoli Wang1 1Department of Psychology, Ningxia University, Yinchuan City, Ningxia, People’s Republic of China; 2Department of Psychology, Shanghai Normal University, Shanghai, People’s Republic of China Abstract: The study aimed to investigate the effects of loving-kindness meditation on positive emotions, intragroup interactions, and complex understanding of others. A total of 50 freshmen not receiving any training in meditation intervention were randomly divided into the meditation group (25 subjects) and the control group (25 subjects). The meditation group was implemented with group meditation intervention for 4 weeks, three times a week, about 30 minutes each time. The results revealed that the effect sizes in interpersonal interaction and complex understanding of others in the meditation group were both above 0.8, indicating strong effects. It was concluded that loving-kindness meditation can effectively improve positive emotions, interpersonal interactions, and complex understanding of others in college students. Keywords: positive emotions, intergroup interactions, loving-kindness meditation, positive rate, complex understanding of others